Current situation in relation to parasites and measures of struggle against them in Russia and cis countries (based on materials of coordinating reports) - A. V. USPENSKY; E. I. MALAHOVA; T. A. YERSHOVA (Российский паразитологический журнал)
42 scientific Institutions and High Schools were involved in fulfillment of In- terdepartmental and Interstate programs in 2013. In all regions of Russian Federa- tion and CIS countries were conducted regular monitoring studies on epizootic sit- uation in relation to parasitosis in domestic and wild animals, birds, fish and bees. Based on information system of collecting and analysis of data a monitoring me- thodology of parasitic diseases is elaborated that allows to forecast the develop- ment of epizootic situation and to optimize the struggle against parasitic diseases within particular region. Forecast of epizootic situation on main helminthosis of animals made for 2013 is basically confirmed. Compared to the previous year the epizootic situation got worse in relation to paramphystomatosis in Yakutia, strongi- latosis of gastrointestinal tract and lungs in Southern Siberia and in the Far East as well as in regions infected with eurytremosis and orientobilharciosis. Parasitic fau- na, spread of parasitosis and features of parasitosis course in ruminants (cattle, sheep, goats and deers) are studied on the territory of Moscow, Kalinigrad, Ryasan, Samara and Tyumen regions, Altai, South Ural, North Caucasus, Yakutia, West Kazakhstan, Central and South-Eastern Tajikistan. Features of parasitosis course in carnivorous in Black Earth and Non-Black Earth zones, Krasnodar Krai and Altai are studied. Continuous monitoring studies in regions unfavorable for trichinellosis are being conducted. Features of circulation of trichinellosis in natural biocenosis of Central region of Russia are investigated and methodical guidelines for its pre- vention in hunting farms are developed where a wide range of issues is embraced. A new patented device «Gelmi» is destined for release of eggs and larvae from helminths using peptolysis of muscle tissue samples; a digestion technique for the detection of trichenellosis and opisthorchosis is developed. Furthermore for the first time metacercariae opisthorchis, mesocercariae alaria and larvae of trematodes using a method of peptolysis are released. Techniques for axonomic identifying of genotype of northern isolates of Trichinella spp. on the territory of RF are devel- oped that allows to complete the system characteristic and to detect phylogenetic relationship inside different taxonomic groups. Helminthophauna of predators on the territory of Central Black Earth State Biosphere Reserve are analyzed. Age- related and season infection dynamics are revealed in main commercial fish in Tsimlyansk, Varvarovka, Karpovka reservoirs as well as in Volga and Lena rivers. Monitoring of spread of invasions and infections in honey bees in the South of Tyumen region is conducted